Family Incivility and Job Performance: A Moderated Mediated Model of Psychological Distress and Core Self-evaluation - Lim, Sandy (Institutional Knowledge at Singapore Management University, 2014)
This study extends the stress literature by exploring the relationship between family incivility and job performance. We examine whether psychological distress mediates the link between family incivility and job performance. We also investigate how core self-evaluation might moderate this mediated relationship. Data from a 2-wave study indicate that psychological distress mediates the relationship between family incivility and job performance. In addition, core self-evaluation moderates the relationship between family incivility and psychological distress but not the relationship between psychological distress and job performance. The results hold while controlling for general job stress, family-to-work conflict, and work-to-family conflict. The findings suggest that family incivility is linked to poor performance at work, and psychological distress and core self-evaluation are key mechanisms in the relationship.